The impact of opioid analgesic prescription uptake on the costs of recovery from injury: Evidence from compensable orthopaedic road trauma patients. (August 2018) - Hahn, Youjin; Tiernan, Gemma; Berecki-Gisolf, Janneke
Highlights: We estimated the effect of opioid uptake on the recovery costs of orthopaedic road traffic injury in Victoria, Australia. Opioid prescription recipients incurred greater compensation costs than non-opioid users. Income compensation was the primary driver of the claim cost difference. Abstract: Long-term opioid prescribing after compensable orthopaedic injury may contribute to the 'long right tail' in the cost of recovery. The aim of this study was to estimate the effect of prescription opioid uptake on injury compensation cost, using orthopaedic road traffic injury claims data from Victoria, Australia. We used a maximum likelihood estimation that accounts for potential endogeneity associated with opioid uptake, utilizing information on the doctor's differential propensity to prescribe opioids when treating other compensable injury patients. Our results suggest that opioid recipients incurred significantly greater hospital costs, income compensation payments, and medical and paramedical expenses. Overall, income compensation was the primary driver of the claim cost difference between opioid recipients and non-recipients. The findings imply that there is scope to impose restrictions on long-term opioid usage, and to encourage the use of alternative pain relief medicines.